(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
It may seem strange to ask the question of the value of education at a university. It is still considered to be the one institution that exclusively awards the highest degrees of education that can ever be achieved. At the same time, fundamental changes can be noted which, in the course of the so-called Bologna Process, have promoted a formal alignment of country-specific educational systems from a purely political-economic point of view. The relevant education policy decision-makers agreed on this and have since confirmed their willingness to comprehensively adapt the education sector to the requirements of the global capitalist economic order and to organize it as a contribution to international competitiveness. Problem Statement. The now 49 signatory states in the European Higher Education Area - Austria has been part of this area since 1999, Armenia joined in 2005 - committed themselves to ensuring the employability of graduates through appropriate reforms in education system and guarantee mutual recognition of degrees that should provide for increased mobility of their populations. The effects have become very tangible for all of us. With the modularization of Bachelor’s and Master’s degree programs, the definition of quality standards, the introduction of the European Credit Transfer System (ECTS) and quality assurance in teaching and development of universities, the degrees were made comparable and at the same time in line with the market. Education has become the commodity with which the individual may act in the Higher Education Area. It has a Market Value. Short analysis of current researches and publications related to the problem. In this politically expansive labor and employment market, individuals can now try their luck with the educational qualifications they have achieved. It also means that they have to be comparable with a larger number of applicants for a job and employment position. In the job market, there is initially an abundance of well-trained but unsolicited people, who turn into a shortage for the same reason. "If everyone’s graduated from high school, nobody really has the graduation!" In economic service companies and state institutions are in the sequence of jobs rarely or completely disappear, which does not make the graduation to the employment requirement. Because of this, school and college degrees, which for a long time were regarded as a kind of insurance for privileged positions in the labor market, today are much more like an "Option [...] traded on the stock market", a commodity with an early "expiration date" and " enormous pressure for innovation "(see Gruschka 2009, p.109). Even with the greatest individual training effort, many in this competition - which inevitably generates losers alongside winners - do not reach their goal. The oversupply of academics, on the other hand, also creates new freedoms in the selection and filling of jobs. The remainder is regarded as an "academic precariat" and is far more or less imaginatively reflected in its life, far below its level of education level is concerned in the diverse and differentiated range of service sector. Research novelty. Although the life chances are linked to education and school leaving or university degrees, they are apparently far from being guarantees of getting into a job or employment relationship at all, let alone that one corresponds to the level of education and training. Regardless of this, for many existentially threatening contexts education still exists in contrast to it as an independent value - more or less idealized. The complaint about the "practice of un-education" (Liessmann 2016) implicitly or explicitly takes up elements of a "true" education to highlight the questionable transitions associated with the above mentioned profound reforms of education. There is no doubt that education has a value that differs from its market value. Something of this value still appears even where general knowledge or general education is required, which can be used in various formats of media entertainment, in quiz broadcasts, for example, concert tickets, shopping vouchers can win or lose up to one million euros. My untimely thoughts are not exhausted in further complaints about the mismatch of the two sizes. At the beginning there is a somewhat unusual literary comparison under the headline "How much education does a human being need?" with exemplary references to how education is currently being discussed. The spectrum ranges from enthusiastic statements about the global and individually life-time expansion of educational processes under the keyword "Lifelong Learning" to more sceptical or questionable time diagnoses, which see this expansion as a rather problematic development. In the discussions, a contrast always flashes, which will then occupy us in a second step: the contrast between "mere" qualification and "true humanistic" education or, briefly, between training and education. In the memory of some almost forgotten insights, I want to show that the contrast itself had only a relative weight, even for the protagonists of one and the other position. The two sides - training and education - were originally not seen as contradictory and incompatible. Only in retrospect did it present itself in this way and it is sporadically deliberately exaggerated.